Identification of Endophytic Fungi of Balangeran (Shorea balangeran Korth.) by Morphological Characterization - Yunik Istikorini; Okta Yulia Sari (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
Endophytic fungi are the potential biological agent that could stimulate plant growth and inhibit plant disease. The existence of diverse and abundant endophytic fungi encourages continuous exploration. One of the plants that have potential as a source of endophytic fungi is balangeran (Shorea balangeran Korth.). The study aimed to identify the species of endophytic fungi from the leaf and twig of S. balangeran based on morphological characteristics. Fungi isolation was conducted by multiple sterilizations and purification. Furthermore, the macroscopic and microscopic morphological characteristics of the endophytic fungi isolates were also identified. The results showed nine colony characteristics of endophytic fungi. Endophytic fungi of Colletotrichum sp1. (SbD 1.1), Phomopsis sp. (SbD 1.3.1), Colletotrichum sp2. (SbD 1.3.2), and Beauveria sp. (SbD 3.1) were only found on the leaves, while Aspergillus niger (SbB 5.1), Colletotrichum sp3. (SbB 5.2), and Nigrospora sp. (SbB 5.3.2 and SbB 6.3) were only found on the twigs. Endophytic fungi Phyllosticta sp. (SbD 1.2) were found in the leaves and twigs. The growth rate of endophytic fungi showed that Colletotrichum sp3 (SbB 5.2) was the fastest, and Phyllosticta sp. (SbD 1.2) was the slowest among the nine isolates. Endophytic fungi that have been isolated will be analyzed for their benefits as a biological agent in future research. Keywords: endophytic fungi, identification, morphological characterization, Shorea balangeran